2001
DOI: 10.1038/35073574
|View full text |Cite|
|
Sign up to set email alerts
|

Sustainability of three apple production systems

Abstract: Escalating production costs, heavy reliance on non-renewable resources, reduced biodiversity, water contamination, chemical residues in food, soil degradation and health risks to farm workers handling pesticides all bring into question the sustainability of conventional farming systems. It has been claimed, however, that organic farming systems are less efficient, pose greater health risks and produce half the yields of conventional farming systems. Nevertheless, organic farming became one of the fastest growi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
233
1
10

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 551 publications
(261 citation statements)
references
References 15 publications
9
233
1
10
Order By: Relevance
“…The conclusions do not always identify one system of production as best, as they depend, for example, on the assessment methods and environmental indicators employed. However, organic production is generally considered the most ecologically sustainable favourable option (Granatstein and Kupferman, 2006), and integrated production is viewed as resulting in the most efficient use of resources per unit of product (Reganold et al, 2001). In general, fruit production is regarded as a sector with a low environmental impact compared to herbaceous cultivation (Granatstein and Kupferman, 2006) and other agri-food sectors (Carlsson-Kanyama et al, 2003;Garnett, 2006;Cuadra and Bjorklund, 2007;Frey and Barrett, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conclusions do not always identify one system of production as best, as they depend, for example, on the assessment methods and environmental indicators employed. However, organic production is generally considered the most ecologically sustainable favourable option (Granatstein and Kupferman, 2006), and integrated production is viewed as resulting in the most efficient use of resources per unit of product (Reganold et al, 2001). In general, fruit production is regarded as a sector with a low environmental impact compared to herbaceous cultivation (Granatstein and Kupferman, 2006) and other agri-food sectors (Carlsson-Kanyama et al, 2003;Garnett, 2006;Cuadra and Bjorklund, 2007;Frey and Barrett, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In general, fruit production is regarded as a sector with a low environmental impact compared to herbaceous cultivation (Granatstein and Kupferman, 2006) and other agri-food sectors (Carlsson-Kanyama et al, 2003;Garnett, 2006;Cuadra and Bjorklund, 2007;Frey and Barrett, 2007). The environmental costs of fruit growing have been studied in terms of the consumption of resources (e.g., water, soil, air, energy) or in terms of various impacts (e.g., pollution, risks to human health and to the eco-system, reduction of bio-diversity) (Reganold et al, 2001). Some recent studies have attempted to assess the total environmental cost of various fruit species throughout their entire life cycle by applying the LCA criteria (Mila i Canals and Clemente Polo, 2003;Mouron et al, 2006), analysis of the associated ecological footprint (Cerutti et al, 2010), or other methods of evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…While some authors found no substantial differences between apples from organic and integrated orchards in terms of yield and fruit size [2,3], others have reported an overall better quality of organic apples compared with integrated or conventional apples [4][5][6]. However, organic yields were inconsistent, probably as the result of unsatisfactory crop load management, higher pest occurrence and weed pressures, as well as lower leaf and fruit tissue nitrogen levels [5].…”
Section: Introductionmentioning
confidence: 99%
“…Integrated farming systems reduce the use of chemicals by integrating organic and conventional production methods and have been successfully adopted on a wide scale in Europe [1]. Organic management practices combine traditional conservation-minded farming methods with modern farming technologies but exclude such conventional inputs as synthetic pesticides and fertilizers, plant growth regulators, and genetically modified organisms [2].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the aim of some recent research includes the comparison of organic farming systems with conventional ones on the base of appropriate ASIs. (Reganold et al, 2001;Mader et al, 2002;Caporali et al, 2003). Results of this kind of research are easily shown graphically, with the help of a so called sustainability polygon or web, that simultaneously displays scores for different indicators and avoids having to aggregate across different scales.…”
Section: Implementation Of Sustainable Agricultural Systems Researchmentioning
confidence: 99%